Features of the Design of Residential Buildings - Keldiyar, Khudayberdiyev; Khosiyat , Tashmatova (Sustainable Civil Building Management and Engineering Journal, 2024)
The article discusses each type of residential and public buildings has its own spatial planning solution, the design of which reflects a rather complex workflow. When designing multi-family residential buildings, economic factors are primarily taken into account. In particular, the construction of residential buildings in Uzbekistan has its own historical tradition. The houses were built in two versions -national and European. These houses mainly consist of houses with separate courtyards. This study employs a qualitative research approach, drawing insights from architectural literature and historical records to examine the design features of residential buildings in Uzbekistan. Data collection involves literature review, analysis of architectural plans, and examination of historical documents. The analysis reveals that the design of multi-family residential buildings is influenced by various factors, including economic considerations, cultural heritage, and historical traditions. In Uzbekistan, the architectural landscape reflects a blend of national and European styles, each with its own spatial planning solutions and design elements. Traditional houses with separate courtyards not only provide privacy and security but also contribute to the overall aesthetics of residential neighborhoods. Additionally, economic factors play a significant role in shaping the design process, with cost-effective construction methods and materials being prioritized in residential building projects.